Deciphering the omicron variant: integrated omics analysis reveals critical biomarkers and pathophysiological pathways - Qianyue Yang; Zhiwei Lin; Mingshan Xue; Yueting Jiang; Libing Chen; Jia-Hong Chen; Yuhong Liao; Jiali Lv; Baojun Guo; Peiyan Zheng; Huimin Huang; Baoqing Sun (2024)
The rapid emergence and global dissemination of the Omicron variant of SARS-CoV-2 have posed formidable challenges in public health. This scenario underscores the urgent need for an enhanced understanding of Omicron's pathophysiological mechanisms to guide clinical management and shape public health strategies. Our study is aimed at deciphering the intricate molecular mechanisms underlying Omicron infections, particularly focusing on the identification of specific biomarkers.